The Essential Guide to Public Health and Health Promotion - Thompson, Susan R. (Susan Rosemary), 1961- (New York : Routledge, 2014)
"Public health is everyones business in the twenty-first century. Health professionals are well placed to provide advice to their clients especially in respect to lifestyle change, but public health initiatives are also supported by a range of voluntary organisations and health workers, ranging from smoking cessation advisers to health trainers and nutrition assistants. Designed to help readers develop the practical skills they need to become effective public health practitioners, this concise text gives an easily digested overview of public health and health promotion theory in accessible language and diagrams, before moving on to the ways readers can apply this in practice. Providing an opportunity for practitioners to understand possible barriers to lifestyle change, debate health inequalities and responsibilities, and explore the role of the media in changing attitudes, it outlines the roles of specific organisations involved in public health work. Covers health needs assessment, agenda setting and the technical aspects of how to research plan and evaluate effective practice either with individual clients or when devising programmes and initiatives for population groups. Details methods of helping people with motivation for lifestyle change, building rapport, ongoing support, monitoring and signposting to specific services. Discusses role of neighbourhoods and communities in improving health and how workers may support local populations to improve the health of their community. Practical Health Promotion and Public Health is an accessible introduction to the principles and practice of health promotion and public health for all those new to working or studying in the area, whatever their professional background"--
Includes bibliographical references and index.
Keywords: Public health; Health promotion; Public health practice; Health promotion